Konvergenz gegen logarithmische Verteilungsgesentze - Bakštys, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бакштис. Сходимость к логарифмическим законам распределения A. Bakštys. Konvergavimas prie logaritminių pasiskirstymo dėsnių